Pendampingan Penelusuran Minat, Bakat, Hobi dan Passion Siswa di SMKN 1 Sijunjung - Maivalinda, Maivalinda; Sulistianingsih, Henny; RC, Rita Srihasnita; Mariyanti, Eka; Abdilla, M.; Eriend , Dion (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The search and development of self-potential can be honed through interests, talents, hobbies and passions so that they can be developed optimally. The purpose of this community service activity is to bring out the potential and competence of SMKN 1 Sijunjung students. The service method with the Holland test which is better known as RIASEC (Realistic, Investigative, Artistic, Social, Entrepreneurial and Conventional). The results of the community service activity can identify students' potential and bridge their learning activities with interests, talents, hobbies and passions. This is done to see the choice of majors when they go to college later and their future careers. The results obtained are that most students have chosen the right major according to their interests and talents. A small number of others are still hesitant and have not realized the potential and competence they have so they need direction to be able to choose the right major and career in the future.